Impact of Demographic Shifts on Family Structures and Social Policy - Srivastava, Gajendra; Rajesh, Sanjay Kumar; Aggarwal, Kalra Vishnubhatla (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
India is experiencing significant demographic shifts, including a growing elderly population and a decline in the traditional extended family structure. By 2050, individuals aged 60 and above are projected to comprise 19% of India's total population, presenting challenges to social cohesion and healthcare systems. This study analyzes these shifts, focusing on aging trends, family structure transformations, and their social implications. Utilizing a mixed-methods approach, the research combines demographic data analysis and in-depth interviews with 40 participants, including policymakers, sociologists, urban planners, and older adults from both urban and rural areas. Findings reveal a transition from extended to nuclear families, particularly in urban regions, resulting in greater vulnerability for older adults due to social isolation and caregiving gaps. The study calls for policies targeting elderly healthcare, and intergenerational support. Recommendations include enhancing healthcare services for older adults, improving pension schemes, and prioritizing age-friendly urban planning. Despite limitations such as small sample size and geographical focus, this research provides valuable insights for policymakers. Future studies should investigate the broader societal impacts of aging, particularly in healthcare, education, and economic productivity, and explore the role of technology in elder care, especially in rural areas.